Techno-Economic Comparison of a Large-Scale Nuclear Power Plant, Small Modular Reactors, and Wind and Solar Power Plant Deployment - Sanja Milivojevic; Milan M. Petrovic; Vladimir D. Stevanovic; Jovica Riznic; Milos Lazarevic (Energies)
A comparison of the net present value, the payback period, and the levelized cost of electricity for three different projects of construction and exploitation of plants for electricity production with the aim of decarbonizing the energy sector is conducted. The first project is the building of a large-scale nuclear power plant with a light-water reactor, the second one is the deployment of several identical small modular reactors, and the third project is based on solar and wind power plants. Given that the sun and wind are intermittent renewable energy sources, it is inevitable to take into account the construction of an energy storage facility in the last project. The results show that the most profitable are the small modular reactors, while the investment into solar and wind power plants is burdened with the necessary electricity storage plant costs. Another drawback of an investment in solar and wind power plants is their shorter exploitation lifetime of 25 years compared to the long-term operation of nuclear power plants of 60 years or even more.